MANAJEMEN KONFLIK DITINJAU DARI KEPRIBADIAN INTROVERT DAN EKSTROVERT - Inayah, Fitri; Putra, Johan Satria (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2017)
This study aims to examine the correlation between conflict management and personality types. The other aim is to examine the difference of conflict management style between the extrovert and introvert personality. The subject of this study are 63 students at social class on XIIth level in MAN 2 Bekasi City, contains of 23 male and 40 female. EPI (Eysenck Personality Inventory) with 56 items was used to divide the subject into the extrovert and introvert personality. Conflict management is measured with the modified version of 30 items CRSI (Conflict Resolution Styles Inventory). The results showed that the means of subject with extrovert personality type is 31,74, while the introvert one is 31,32. Pearson correlation test showed that p = 0,429 (p > 0,05) which means that no correlation between conflict management and personality types. Comparation by t-test result is p = 0,669 (p > 0,01), which means there is no difference of conflict management style between subjects with extrovert and introvert personality types. The limitation of this study including the validity and reliability of the conflict management scale, the homogeneity of subjects, and the little number of sample